Łódź: Essays on literature, space and history - Cieślak, Tomasz (Lodz University Press, 2023)
The book is a collection of studies presenting the specificity of the experience of modernity in Łódź against the background of other cities – manufacturing centers of the second industrial revolution in Europe. The publication analyzes the representation of Łódź’s space in literature, from the 1880s to 1939, in literary works written in Polish, Yiddish, German and Russian, which results from the multicultural character of the city. The author takes into account, to a lesser extent, selected recent works. He uses both the most outstanding and forgotten texts, he also reaches for journalistic texts and popular literature. The main idea and compositional axis of the book is the reconstruction of the components of the “Łódź text” (following Vladimir Toporov’s “Petersburg text”). The development of the “Łódź text” is related to the most important events in the history of the city presented chronologically: the revolution of 1905–1907, World War I, and the Great Depression, because they had a decisive impact on building local identity. The “Łódź text”, shaped at the turn of the 19th and 20th centuries, turns out to be, in the light of analyses, still present and productive for subsequent generations of authors.